2008
DOI: 10.1902/jop.2008.070038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Putty‐Form Hydroxyapatite Matrix Combined With the Synthetic Cell‐Binding Peptide P‐15 on Alveolar Ridge Preservation

Abstract: A favorable response was observed when Putty P15 was applied to extraction sockets, suggesting that it may be useful for alveolar ridge preservation prior to dental implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
3
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 46 publications
1
77
3
7
Order By: Relevance
“…It has also been implemented in endodontic surgeries as a concomitant treatment during management of the endodontic-periodontal lesions (1)(2)(3)(4)(5)(6)(7). The function of GTR is to place a barrier membrane over the denuded root surfaces and the debrided periodontal defect to exclude epithelial growth and to allow specifically periodontal ligament and alveolar bone cells to repopulate the isolated space (8,9).…”
mentioning
confidence: 99%
“…It has also been implemented in endodontic surgeries as a concomitant treatment during management of the endodontic-periodontal lesions (1)(2)(3)(4)(5)(6)(7). The function of GTR is to place a barrier membrane over the denuded root surfaces and the debrided periodontal defect to exclude epithelial growth and to allow specifically periodontal ligament and alveolar bone cells to repopulate the isolated space (8,9).…”
mentioning
confidence: 99%
“…Theoretical data was confirmed by clinical outcome (22). In fact, according to several studies (23)(24)(25)(26), new generation hydroxya- (27). Moreover, the osseointegration period was confirmed to range between 9 and 18 months.…”
Section: Discussionmentioning
confidence: 65%
“…Nine months after tooth extraction, they reported no reduction in ridge height and no change in ridge width. Neiva et al (2008) in a 24 patient study over 4 months compared an anorganic bovine-derived hydroxyapatite matrix combined with a synthetic P-15 Putty (PepGen P-15 Putty®) and a bioabsorbable collagen wound dressing (CollaPlug®) to a bioabsorbable wound dressing alone. Neiva reported a loss of 1.31 mm in ridge width and a gain of 0.15 mm in ridge height for the Putty PIS group.…”
Section: Human Extraction Socket Healing Sequencementioning
confidence: 99%
“…Zitzmann et al (1997Zitzmann et al ( ,2001) reported similar results, in a 6-month study of 6 sockets grafted with BioOss®, 27% vital bone, 30% non-vital bone, and 43% trabecular space. Neiva et al (2008), in a 24 patient study, compared a putty-form anorganic bovine-derived hydroxyapatite matrix combined with a synthetic cell-binding peptide P-I5 (Putty PI5) to a bioabsorbable collagen membrane to a bioabsorbable collagen dressing alone. He reported that the Putty PI5 had 29.92% vital bone, 65.25% bone marrow and 6.25% non-viable bone.…”
Section: Xenograft Studiesmentioning
confidence: 99%